Nutritional and educational intervention to reducemalnutrition due to excess in university students - Torres-Zapata, Angel Esteban (Horizonte Sanitario, 2021)
Objective: To assess the effect of a nutritional/educational intervention over malnutrition due to excess in university students. Materials & Methods: A quantitative study with a descriptive approach and an experimental design was employed. Intervention was conducted through the implementation of educational strategies promoting healthy lifestyles, nutritional status of participants was monitored throughout the entire scholar cycle (16 weeks). Non-probabilistic sampling was used including 52 university students who willingly accepted to participate. Data was processed using descriptive statistics (frequency, category variable percentages, measures of central tendency, dispersion for numerical variables). Nutritional profiles of the participants were evaluated based on the normality of the data through the use Kolmogorv Smirnov test, averages, T tests for related samples and the Wilcoxon test to evaluate the intervention effects. Results: Weight average on the pre-intervention stage was 74.7 kg and 68.2 kg post intervention. Before intervention 42.31% (32.69/9.62) presented overweight or obesity, after intervention a thus 17.3% (15.38/1.92) presented overweight or obesity which signifies a decrease of 25. 01 % was recorded (p value < 0.001) Conclusions: Educational intervention had an impact on the nutritional status of university students in relation with the percentage of obesity and overweight the ratio of normal weight students was increased. Key Words: Educational intervention, Obesity, Nutritional Profile.